Motor Vehicle Fuel Tax Effectiveness And Contribution To Regional Original Revenue Managed Bpprd Provsu - Eni Saputri; Juliana Nasution (Jurnal Riset Perpajakan: Amnesty, 2022)
This study aims to determine the effectiveness and contribution of motor vehicle fuel taxes to Regional Original Revenue managed by the BPPRD of North Sumatra Province in 2017 to 2021, to determine the causes of not achieving the motor vehicle fuel tax target and the efforts that must be made to optimize PBBKB. This study uses a qualitative research with a descriptive approach. The data used by researchers are quantitative and qualitative data. Data collection techniques used are observation, interviews and documentation. The results showed that the percentage of the effectiveness of the motor vehicle fuel tax in 2017-2020 fluctuated and in 2020 the realization did not reach the target with effective criteria. As for the contribution to Regional Original Revenue, in 2017-2021 it fluctuated and the contribution criteria were declared to be less contributing every year. The factor causing the PBBKB target has not been achieved, namely the 2020 APBD changes which increased to Rp.882,786,893,431 with the realization of Rp.812,843,402,651 or 92.08%. Efforts must be made to optimize PBBKB, namely issuing Governor Regulation No. 1 of 2021 contains tariff increases and reconciliation, especially with Pertamina